Meningkatkan Sikap Sosial Melalui Penerapan Model Pembelajaran Value Clarification Technique - Siti Nurasiah (Al-Aulad: Journal of Islamic Primary Education, 2019)
This study aims to determine the social attitudes of students before and after using the value clarification technique (VCT) learning model. The research method used is Classroom Action Research which consists of planning, implementing, observing, and reflecting which lasts for two cycles, with the subject of class V MI Nurul Yakin, amounting to 17 students. Before using the VCT learning model, the average percentage of students' social attitudes reached 47% (less). After using the VCT learning model the average percentage of students' social attitudes in the first cycle reached 58% (less), while in cycle 2 the average percentage of students' social attitudes reached 78% (good). There were changes in the students' social attitudes in the learning process by applying the VCT learning model to the subject matter of the Akhah Akhlak the subject fosters harmony with neighbors and society.